Prognostic model for the development of cardiomyopathies based on genetic predictors - S. Yu. Nikulina; O. O. Kuznetsova; G. V. Matyushin; A. A. Chernova; V. N. Maksimov (Российский кардиологический журнал, 2024)
Aim. To develop a prognostic model for the development of primary and secondary cardiomyopathy based on genetic predictors.Material and methods. The study included 221 patients with cardiomyopathy. The mean age of the participants was 55,30±9,69 years, with the age range from 20 to 77 years. Two following groups of patients were determined: the first group (n=111) with idiopathic dilated cardiomyopathy (DCM) and the second group (n=110) with ischemic myocardial dilation. DNA was extracted from the venous blood of all participants using phenol-chloroform extraction for subsequent genotyping using polymerase chain reaction and restriction fragment length polymorphism analysis.Results. The performed multivariate analysis using the stepwise selection method showed a significant effect of the following predictors at the third step: AG/GG allelic variant of the SCN5A gene (rs1805124), 6a/6a allelic variant of the MMP3 gene (rs35068180) and the patient's age.The performed multivariate analysis using the stepwise selection showed a significant effect of the following predictors: AG/GG allelic variant of the CTLA4 gene (rs231775), AA and AG allelic variants of the SCN5A gene (rs1805124).Conclusion. Genetic studies on cardiomyopathies reveal significant associations between certain single nucleotide polymorphisms and the risk of disease development. The study results showed that the AG/GG allelic variant of the SCN5A gene (rs1805124), 6a/6a allelic variant of the MMP3 gene (rs35068180) and the patient's age have prognostic significance in the development of DCM. In addition, AG/GG allelic variant of the CTLA4 gene (rs231775), AA and AG allelic variants of the SCN5A gene (rs1805124) have prognostic significance in the development of ischemic myocardial dilation.